Memórias e experiências do espaço: Práticas fotográficas na Arquitectura - Inês Lourenço Azevedo (2021)
Since the beginning, human beings have seen a special interest in representing the world and creating a register that perpetuates reality. Initially, this connection arises from drawing, sculpture and painting. Later, photography emerges that allows a representation closer to the real. At the beginning of photography, the process was unraveling, for which Architecture was the ideal object to photograph, given its immobility. Since then, architecture and photography complement each other. Photography quickly became one of the main means of communication between people, it also significantly influenced the relationship between space and its transformation. This reveals the importance of photography in architecture, which is considered an instrument of exploration, understanding and dissemination. In fact, the rapid dissemination of photography through the media and its availability to be used by all people has resulted in making Architecture accessible to the whole world, making it unnecessary to visit the work in order to get to know it. Despite arousing different opinions among architects, most of them quickly recognized the potential of photography, leading them to use it. In this context, aiming to understand the joint work between photographers and architects, it was decided to study two Portuguese architecture photographers, who establish a very close relationship with photography and architecture. Inês d'Orey and João Morgado represent different ways of perceiving space and, although their photographs reveal their own identity, their images do not limit the multifaceted richness of the architectural space, nor the freedom of interpretation of the observer. In fact, "it is in the fact that photography has the power to make the observer believe that the Architecture it represents through its imagery, created from the lens of a camera has certain qualities where its potential resides." 2 Later, it was decided to study some of the photographers works, in order to understand their different forms of photographic expression. After the literary review, the critical and exploratory study on the work of the selected photographers a basis was created that served the practical case. This being constituted by a visual narrative to the stations of Metro da Trindade and Estádio do Dragão and transmit, among other things, the different dynamics present in these spaces in a difficult time of isolation and crisis. Metro stations are public spaces that daily bring together a greater number of people in different uses, being essentially spaces for circulation and exchange. The Porto metro stands out for its surface stations, which implies an even more careful and thought-out urbanization plan so that the city can continue its growth and evolution, without barriers associated with them.